2003
DOI: 10.1037/0090-5550.48.2.93
|View full text |Cite
|
Sign up to set email alerts
|

The Americans With Disabilities Act Knowledge Survey: Strong psychometrics and weak knowledge.

Abstract: Objectives: To construct and validate a measure that assesses knowledge of the Americans With Disabilities Act (ADA) and to examine ADA knowledge among private and public sector representatives. Study Design and Subjects:A 20-item measure was developed and administered to undergraduates (n ϭ 210) and ADA experts (n ϭ 34) to establish validity and reliability. Then, it was administered to 133 private and public sector representatives. Results: The ADA experts obtained a significantly higher mean than undergradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…The results of this study supported the findings of two previous studies that measured the level of academic attainment on the knowledge of disability rights by Hernandez et al (2003) and Clarke and Crewe (2000). Hernandez et al (2003) concluded that higher level of academic attainment, those with college or graduate level of education obtained a significantly higher level of knowledge of disability rights law and legislation than those who only had high school or trade school education. Clarke and Crewe (2000) concluded that master's level rehabilitation students were found to have a higher level of ADA knowledge than employers or regular college students.…”
Section: Research Question 3 -Knowledge and Attitudes Correlationssupporting
confidence: 82%
See 4 more Smart Citations
“…The results of this study supported the findings of two previous studies that measured the level of academic attainment on the knowledge of disability rights by Hernandez et al (2003) and Clarke and Crewe (2000). Hernandez et al (2003) concluded that higher level of academic attainment, those with college or graduate level of education obtained a significantly higher level of knowledge of disability rights law and legislation than those who only had high school or trade school education. Clarke and Crewe (2000) concluded that master's level rehabilitation students were found to have a higher level of ADA knowledge than employers or regular college students.…”
Section: Research Question 3 -Knowledge and Attitudes Correlationssupporting
confidence: 82%
“…In fact, only 18% of faculty members said they were familiar with section 504 of the Rehabilitation Act and only 50% said they were familiar with the ADA, both of which protect the rights of students with disabilities (Thompson & Bethea, 1997). Furthermore, in the validation studies of the ADA Knowledge Survey instrument by Hernandez et al (2003), the mean score on the ADA Knowledge Survey among students was 9 (SD = 3.6) out of a possible score of 20 as compared to the mean score of ADA expert of 17.2 (SD = 2.3). Clarke and Crewe (2000) found Masters level rehabilitation students to have a higher level of ADA knowledge than employers or regular college students.…”
Section: Knowledge Of Disability Rights: a Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations